ANALISIS NILAI TAMBAH USAHA PENGOLAHAN IKAN ASAP (LELE DAN PATIN) DI KOTA PALEMBANG (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
Catfish and catfish are freshwater fish commodities that are a source of animal protein consumed by all levels of society because they are easy to obtain at affordable prices. The process of processing catfish and catfish into smoked fish can be done in a modern and traditional way. The most basic difference between these two methods lies in the main ingredients in the manufacture of the smoker. Smoked fish (catfish and catfish) have a fairly high protein content, so these processed products are beneficial for the health of all ages who consume them. The city of Palembang has one of the MSMEs engaged in processing smoked fish (catfish and catfish) in Tegal Binangun Village, Plaju Darat Village, Plaju District. This study aims to determine the income of the smoked fish (catfish and catfish) processing business in the city of Palembang, to determine the added value of the smoked fish (catfish and catfish) processing business in the city of Palembang, and to assess the financial feasibility of the smoked fish (catfish and catfish) processing business. catfish) in Palembang City. The method used in this research is a case study. The case study method is an activity to collect data and information by observing all elements of the population. The sampling method used in this study is the purposive sampling method (deliberately).The results showed that the income of processing smoked fish (catfish and catfish) Mr. Bunyamin was Rp. 1,501,386.30/production process, while Pak Samsul was Rp. 598,679.63/production process. The added value generated from Pak Bunyamin's smoked fish processing business is Rp. 2,052,000.00/production process and Mr. Samsul's is Rp. 896,000.00/production process. Keyword: fish, value edded, consumed